Design of Single-Layer Microstrip Antennas for Dual-Frequency-Band Ratio Adjustment with Circular Polarization Characteristics. Issue 4 (19th May 2017) - Lee, Taekki; Choo, Hosung; Jang, Byung-Jun; Byun, Gangil
ABSTRACT: This article proposes the design of a single-layer circular polarization antenna for flexible dual-frequency-band ratio adjustment. The antenna consists of an inner circular patch and an outer ring patch that is electromagnetically coupled to the circular patch. The circular patch is fed by two ports of a hybrid chip coupler, and the dual-frequency-band ratio is adjusted by varying the gap distance between the two patches. For verification, the proposed antenna was fabricated to measure its antenna characteristics in a full anechoic chamber, and the results demonstrated that the antenna is suitable for flexible adjustment of the dual-frequency-band ratio from 1.24 to 1.8, with an average axial ratio of 2.4 dB.